The Impact of IL-18 and IFN-γ on Severity of Malaria and Quality of Treatment - Gholam-Reza Ameri; Kianoosh Malekzadeh; Zahra Noor-Mohammadi; Mohammad Shekari; Habibollah Turki; Hanieh Solaimani (Fasa University of Medical Sciences, 2014)
Background & Objective: In human malaria, genotype of cytokines affect immune system. The impact of genotype -137G/C in IL-18 and +874A/T in IFN-γ on the severity of malaria and the quality of treatment - as factors to form asymptomatic persons in endemic regions- has been investigated.Materials & Methods: 100 patients and 102 healthy persons were evaluated by Nested-PCR and thick blood film. IL-18(G-137C) and IFN- γ (A+874T) were determined by Single Specific Primer-Polymerase Chain Reaction and ARMS-PCR methods, respectively. The results were analyzed statistically.Results: In this research, it has been observed that allele-T in IFN- γ gene and allele-C in IL-8 gene have  protective effects against severity of Malaria. In addition, it has clearly been found that development and growth rate of plasmodium in µl of blood as well as anemia induced malaria significantly reduced in carriers of these alleles (p<0.0001). This effect has also been observed in the quality of the treatment in such a way that no parasite remained at the end of second day of treatment in carriers of alleles IFN- γTT and IL-18CC. Conclusion: These findings issue the impact of immunogenetypes of patients on treatment quality and asymptomatic patients and parasite reservoir as effective factors in endemic malaria. Immunogenetypes of people may play as a remarkable factor to control malaria in endemic areas.